The Prevalence of Hyperuricemia Sharply Increases from the Late Menopausal Transition Stage in Middle-Aged Women - Cho, Sung Kweon (J Clin Med, 2019)
The impact of menopausal transition on change of serum uric acid level remains unknown. The present study evaluated the relationship of menopausal stages with prevalent hyperuricemia in middle-aged women. This cross-sectional study included 58,870 middle-aged Korean women, aged ≥40, who participated in a health examination from 2014 to 2016. Menopausal stages were obtained with a standardized, self-administered questionnaire and were categorized according to the criteria of the Stages of Reproductive Aging Workshop (STRAW+10). Hyperuricemia was defined as a serum uric acid level of ≥6 mg/dL. The prevalence of hyperuricemia increased as menopausal stage increased. The multivariable-adjusted odds ratios (95% confidence intervals) for prevalent hyperuricemia comparing early transition, late transition, and post-menopause to pre-menopause were 1.19 (0.80–1.77), 2.13 (1.35–3.36), and 1.65 (1.33–2.04), respectively. This association was stronger among non-obese compared to obese participants and in those with low high-sensitivity C-reactive protein (hsCRP) levels (<1.0 mg/L) compared to those with elevated hsCRP levels of ≥1.0 mg/L (p for interaction = 0.01). In this large sample of middle-aged women, the prevalence of hyperuricemia significantly increased from the menopausal stage of late transition, independent of potential confounders. Appropriate preventive strategies for reducing hyperuricemia and its related consequences should be initiated prior to menopause.